A Sporazum, avagy föderalista kísérlet a királyi Jugoszláviában : 1939-1941 - Gulyás, László (Közép-Európai Közlemények, 2009)
In Beograd, on the 1st of December, 1918, the first Yugoslavian state was born from separate regions. These regions were absolutely different in several aspects: history, political culture, sodial development, economical performance, language, law system, religion, cultural niveau and traditions. The Serbian political elite that had grasped the administration of the state had to face the following challenge: is the state able to handle the regional differences, is it possible to form a unified state from the regions, or the centrifugal forces will tear the state apart. One of the answers given to this question was the serbian-croatian reconciliation effort of 1939. In our paper we present this effort.